IMPLEMENTATION OF FORMATION TECHNOLOGY OF INFORMATION-DIGITAL COMPETENCE OF JUNIOR SCHOOLCHILDREN IN THE PROCESS OF SOCIAL AND PEDAGOGICAL COMMUNICATION - Стеганцева, Валерия (SWorldJournal, 2021)
The article reveals the importance of information-digital competence for junior schoolchildren in the context of the ideas of the concept "New Ukrainian School". The author highlights the stages of introducing pedagogical technology of the formation of i